2014
DOI: 10.1248/cpb.c14-00305
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anticancer Evaluation of Benzyloxyurea Derivatives

Abstract: A series of novel benzyloxyurea derivatives was designed, synthesized by substituting different benzyls or phenyls on N,N′-positions of the hydroxyurea (HU). These target compounds were evaluated for their anticancer activity in vitro against human leukemia cell line K562 and murine leukemia cell line L1210 in comparison with HU by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Some of the compounds showed promising anticancer activity against the cells. Molecular docking experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The key to make this protocol successful depends on the reduction of acetoxime by Raney Ni catalyst 14. Alternatively, hydrolysis of acetoxime could obtain hydroxylamine derivatives 21…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The key to make this protocol successful depends on the reduction of acetoxime by Raney Ni catalyst 14. Alternatively, hydrolysis of acetoxime could obtain hydroxylamine derivatives 21…”
Section: Resultsmentioning
confidence: 99%
“…[14] Alternatively,h ydrolysis of acetoxime could obtain hydroxylamine derivatives. [21] Based on the above results and pioneering studies, [3f,g,h, 5a, 16, 18d, 22] the mechanism of acetoxime-directed orthoarylationr eaction is proposed as depicted in Scheme 5.To begin with, the Pd II species A,w hich is bound by amino acid ligand,c oordinates with the substrate 1 ands ubsequently activates the ortho-CÀHb ond, forming as ix-membered exo-palladacycle intermediate B. [14] Transmetalation with Ar-BPin 2 produces intermediate C, [18d, 3h] followed by reductive elimination, releases the target molecule 3,w ith concomitant generation of Pd 0 species D.R eoxidation with 2equiv of Ag I regenerates the active Pd II species A foranother catalytic cycle.…”
Section: Resultsmentioning
confidence: 99%
“…The thiourea structure is similar to the urea, except that the S atom in thiourea replaces the O atom on urea. In previous studies, urea was widely used in drug discovery research, for example as anticancer [1,2], anti-tuberculosis [3,4], antimalarial [5,6] and analgesic [7]. Thiourea was also widely used in new drug discovery research, such as anticancer and antitumor [8][9][10][11][12], antibacterial, antimicrobial and anti-tuberculosis [13][14][15][16][17][18], soluble epoxide hydrolase (sEH) inhibitor [19] and antiviral [20].…”
Section: Introductionmentioning
confidence: 99%
“…Of target compounds, one is both 6-substituted purine hydroxamic acids and 6-substituted purine hydroxycarbamides containing hydroxyurea pharmacophore. Our group has made great efforts to develop novel hydroxycarbamides to evaluate their anticancer activity, [32][33][34][35] and found that some hydroxycarbamides possessed potent antitumor activity. To explore the possibility of synergistic effects, we introduced aliphatic diamines to 6-position of purine as linker and synthesized 6-substituted purine hydroxycarbamides, namely, 6-substituted purine hydroxamic acids.…”
mentioning
confidence: 99%